First-Principles Calculations of Shocked Fluid Helium in Partially Ionized Region (Communications in Computational Physics, 2012)
Quantum molecular dynamic simulations have been employed to study the equation of state (EOS) of fluid helium under shock compressions. The principal Hugoniot is determined from EOS, where corrections from atomic ionization are added onto the calculated data. Our simulation results indicate that principal Hugoniot shows good agreement with gas gunand laser driven experiments, and maximum compression ratio of 5.16 is reached at 106 GPa.